2009
DOI: 10.1186/1757-7241-17-3
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric trauma deaths are predominated by severe head injuries during spring and summer

Abstract: Fatal pediatric trauma occurs most frequently in boys during spring/summer, associated with severe head injuries and low probability of survival. Preventive measures appear mandated in order to reduce this mortality in this age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
4
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 25 publications
4
16
4
6
Order By: Relevance
“…[3] In previous reports about pediatric trauma, it is indicated that 67.8% to 68.4% of pediatric patients were male and 32.4% to 31.6% were female [6,10] Soreide et al stated that the mean age was 13 years and Mihalicz et al reported the mean age was 11 years. [11,12] In this study, distribution of gender was similar with previous reports and furthermore female victims significantly younger than male. Also, in this study the mean age was found to be lower than the previous figures.…”
Section: Discussionsupporting
confidence: 78%
“…[3] In previous reports about pediatric trauma, it is indicated that 67.8% to 68.4% of pediatric patients were male and 32.4% to 31.6% were female [6,10] Soreide et al stated that the mean age was 13 years and Mihalicz et al reported the mean age was 11 years. [11,12] In this study, distribution of gender was similar with previous reports and furthermore female victims significantly younger than male. Also, in this study the mean age was found to be lower than the previous figures.…”
Section: Discussionsupporting
confidence: 78%
“…This is due to a variety of factors: differences in incidence, different approaches between centres and regions, and the fact that pancreatic injury is rare and thus few formal studies of the topic have been conducted (3). Concomitant injuries in about 80 % of the children must also be taken into account when choosing a treatment method.…”
Section: Discussionmentioning
confidence: 99%
“…Of all injuries, those occurring most frequently in children are head trauma and extremity injury, and abdominal injuries comprise only about 10 % of the total share (2). A Norwegian study found that among injuries with a fatal outcome, head trauma results in four of five fatalities, and bleeding is the next most frequent cause of death (3).…”
Section: Discussionmentioning
confidence: 99%
“…Blunt injuries dominate in children, they make up between 83-92% (20, 36) of all injuries, and road traffic accidents is the most common cause (36,37). During the first years in life the unintentional injuries are the most common and during the teenage years intentional self-harm increases and becomes the second most common cause of death (22).…”
Section: Injury Mechanism In Different Age Groupsmentioning
confidence: 99%
“…In older age groups most of the injuries happen on the sports and athletic fields, and in older age on the roads (6). The pre hospital child injury mortality is in the range of 54 and 58% in Scandinavia (20,36).The majority of deaths in the working age is located in the pre hospital setting, in Norway 78% has been found to die in the pre hospital setting in the years between 1998 and 2007 (26). In the group of elderly in hospital death is more common (34).…”
Section: Location (Pre or In Hospital)mentioning
confidence: 99%